A probabilistic method for calculating the usefulness of a store with finite energy capacity for smoothing electricity generation from wind and solar power - John Barton; David Infield (2005)
This paper describes a novel method of modelling an energy store used to match the power output from a wind turbine and a solar PV array to a varying electrical load. The model estimates the fraction of time that an energy store spends full or empty. It can also estimate the power curtailed when the store is full and the unsatisfied demand when the store is empty. The new modelling method has been validated against time-stepping methods and shows generally good agreement over a wide range of store power ratings, store efficiencies, wind turbine capacities and solar PV capacities. Example results are presented for a system with 1MW of wind power capacity, 2MW of photovoltaic capacity, an energy store of 75% efficiency and a range of loads from 0 to 3MW average.